2015
DOI: 10.1155/2015/248985
|View full text |Cite
|
Sign up to set email alerts
|

Management of Overweight during Childhood: A Focus Group Study on Health Professionals’ Experiences in General Practice

Abstract: Background. Because of the increasing prevalence of overweight and obesity in childhood in the Western world, focus on the management in general practice has also increased. Objective. To explore the experiences of general practitioners (GPs) and practice nurses participating in a randomised controlled trial (RCT) comparing two management programmes in general practice for children who are overweight or obese. Methods. Three focus groups with GPs and nurses participating in the RCT. Transcribed data were analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 20 publications
(18 reference statements)
0
2
0
Order By: Relevance
“…However, pervious research has found that parents prefer to receive information about child weight status rather than avoid discussing it [21, 30]. Healthcare providers also believe that parents expect to be informed about their child’s weight development [24, 31]. Indeed, a previous study in Sweden has shown that, in most cases, CHC nurses, rather than parents, were those who initiated weight status conversations [11].…”
Section: Discussionmentioning
confidence: 99%
“…However, pervious research has found that parents prefer to receive information about child weight status rather than avoid discussing it [21, 30]. Healthcare providers also believe that parents expect to be informed about their child’s weight development [24, 31]. Indeed, a previous study in Sweden has shown that, in most cases, CHC nurses, rather than parents, were those who initiated weight status conversations [11].…”
Section: Discussionmentioning
confidence: 99%
“… 10 Proactive strategies are needed when childhood has been advocated for, and this would help in prevention of overweight and obesity. 11 Examples of such strategies include promoting a health diet, physical activity, and the subtraction of screen time (watching TV, playing games). This is important in preventing obesity among children in the early period of life and it was also stated in the guidelines pioneered by WHO on the prevention of obesity in children.…”
Section: Introductionmentioning
confidence: 99%